Walory edukacyjne i popularyzatorskie Panteonu Górnośląskiego w Katowicach - Szostek, Bartosz (Kultura-Społeczeństwo-Edukacja, 2024)
The aim of this article is to present the activities of the Katowice Cultural Institution Pantheon Upper Silesia, taking into account educational and popularization values. The author focuses on presenting individual initiatives undertaken by the institution’s employees to demonstrate how a relatively young institution approaches the issue of knowledge transfer and its popularization.